Minimally invasive surgical oncology state-of-the-art cancer management - Matteotti, R.; Ashley, Stanley W. (Springer, 2011)
The past 20 years have witnessed an extraordinarily rapid adoption of minimally invasive surgical techniques, and increasingly these techniques are being employed in the diagnosis and treatment of a wide range of malignancies. This book is designed to serve as a unique and comprehensive overview of the current status of minimally invasive surgery in oncology patients and in addition offers valuable insights into the future of this constantly evolving field. The first section of the book is devoted to essential background information and to explaining what is physiologically distinctive in the cancer patient undergoing laparoscopic surgery. The second section then examines in detail a wide range of clinical aspects and issues across different disciplines, with clear instruction on the use of minimally invasive procedures. The aim is to enable the reader to make treatment decisions appropriate to the individual patient, to carry them out effectively, and to institute suitable postoperative care. Summaries of the latest knowledge in traditional therapies such as chemotherapy are also provided when appropriate. Each chapter is written by a recognized expert, and numerous high-quality illustrations are included to assist understanding. This book will serve both as a clinical reference guide and as an operative atlas, and is certain to prove invaluable in daily clinical practice.